Moduli of multiply-connected domains on a Riemannian Mobius strip - Okhrimenko, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the modulus problem for families of curves in multiply-connected nonorientable domains on a Riemannian Mobius strip. We determine the extremal metric and the modulus of a “cross” family of arcs.